Inhibitory effects of aloe vera extracts on anti-tyrosinase, anti-collagenase and anti-elastase potential - Sacan, Ozlem; Akev, Nuriye; Yanardag, Refiye (Bangladesh Journal of Botany, 2024)
In the present work, in vitro inhibitory effects of aqueous and methanolic extracts of A. vera leaves on tyrosinase, elastase and collagenase, which are enzymes responsible for the maintenance of skin texture were studied. The leaf gel and skin aqueous and methanolic extracts were individually examined for tyrosinase and collagenase inhibitory activities. While the skin methanolic extract was studied only for its elastase inhibitory activity. The inhibitory activity of the extracts increased in a dose–dependent manner. A. vera gel extract showed a promising inhibiton effect for tyrosinase and collagenase activity. The ability of Aloe vera extracts to inhibit tyrosinase, collagenase and elastase suggests their potential use as skin care additived in natural remedies and cosmetics. Bangladesh j. Bot. 53(3): 597-603, 2024 (September)